2015
DOI: 10.1007/s00276-015-1440-9
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of branching of the left portal vein: an anatomo-radiological study

Abstract: Knowledge of the pattern of branching of the left portal vein is important for surgical purpose. CT angiography is a valuable preoperative examination to visualize the branching pattern of adult patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We observed that the mean number of portal branches from LPV to segment I, II, III, and IV were 2, 2, 2, and 8 branches, respectively. Macchi et al found that the range of portal branches to segment II, III, and IV to be 1–3, 1–6, and 4–9, respectively (Macchi et al, ). Unless all the portal branches to the segment to be resected are precisely identified and ligated, the line of demarcation is likely to be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We observed that the mean number of portal branches from LPV to segment I, II, III, and IV were 2, 2, 2, and 8 branches, respectively. Macchi et al found that the range of portal branches to segment II, III, and IV to be 1–3, 1–6, and 4–9, respectively (Macchi et al, ). Unless all the portal branches to the segment to be resected are precisely identified and ligated, the line of demarcation is likely to be inaccurate.…”
Section: Discussionmentioning
confidence: 99%
“…The number of second order branches feeding the segments I, II, III, and IV is actually much more important (Majno et al, ). Despite several studies concerning the branching pattern of the LPV (Macchi et al, ; Maurer et al, ), we decided to reconsider the LPV branching pattern in the human liver.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations